THE RELATIONSHIP BETWEEN FATHER INVOLVEMENT WITH LIFE SATISFACTION IN ADOLESCENTS IN WEST SUMATRA - Anggun Yunita Fitri, Anggun Yunita Fitri (Causalita, 2024)
This study aims to determine the relationship between father involvement and life satisfaction in adolescents in West Sumatra. Life satisfaction is psychological well-being or satisfaction with life as a whole (Santrock, 2012). In addition, according to Argyle (2001) life satisfaction is also subjective well-being because it is subjective according to the individual's assessment. Individual assessment of life satisfaction according to Diener, Oishi, Lucas, and Suh (1999) can be assessed based on Abraham Maslow's theory of need satisfaction, namely physiological, safety, social, esteem, and self-actualization needs. If these five needs can be met properly, individuals will get life satisfaction. Meanwhile, father involvement is parenting by involving fathers in interactions with children through relaxing activities, playing together and teaching something and being responsible for their role in conceptualizing parenting for children. This study uses quantitative methods with a correlational quantitative research design. The population in this study were adolescents in West Sumatra with a total sample of 361 adolescents. data collection tools using life satisfaction scales and father involvement, data analysis using product moment correlation. The results of this study indicate a positive relationship between life satisfaction and father involvement in adolescents in West Sumatra (r = 0.298: p = 0.00).